Synthesis and characterization of 1,3-bis(2-fluorophenyl)-5-pentyl-1,3,5-triazinane - Ferhati, Amel; Bouchemma, Achene; Bouhenguel, Mustapha; Lefrada, Leila; Sid, Assia (European Journal of Chemistry, 2017)
A new triazinane derivative was obtained by condensation reaction of pentylamine, 2-fluoroaniline and formaldehyde (formalin) in basic solution to yield 1,3-bis(2-fluorophenyl)-5-pentyl-1,3,5-triazinane. The structure of the synthesized compound was characterized by spectroscopic methods: FT-IR, UV-Vis, 13C, 19F and 1H NMR.